The Biosynthesis of D-1,2,4-Butanetriol From d-Arabinose With an Engineered Escherichia coli - Wang, Jing; Chen, Qiaoyu; Wang, Xin; Chen, Kequan; Ouyang, Pingkai (Frontiers in Bioengineering and Biotechnology, 2022)
D-1,2,4-Butanetriol (BT) has attracted much attention for its various applications in energetic materials and the pharmaceutical industry. Here, a synthetic pathway for the biosynthesis of BT from D-arabinose was constructed and optimized in Escherichia coli. First, E. coli Trans1-T1 was selected for the synthesis of BT. Considering the different performance of the enzymes from different organisms when expressed in E. coli, the synthetic pathway was optimized. After screening two D-arabinose dehydrogenases (ARAs), two D-arabinonate dehydratases (ADs), four 2-keto acid decarboxylases (ADXs) and three aldehyde reductases (ALRs), ADG from Burkholderia sp., AraD from Sulfolobus solfataricus, kivD from Lactococcus lactis IFPL730, and adhP from E. coli were selected for the bio-production of BT. After 48 h of catalysis, 0.88 g/L BT was produced by the recombinant strain BT5. Once the enzymes were selected for the pathway, metabolic engineering strategy was conducted for further improvement. The final strain BT5Δ5 with gene yiaE, ycdW, and yagE disrupted produced 1.13 g/L BT after catalyzing for 48 h. Finally, the fermentation conditions and characteristics of BT5Δ5 were also evaluated, and then 2.24 g/L BT was obtained after 48 h of catalysis under the optimized conditions. Our work was the first report on the biosynthesis of BT from D-arabinose.